Perbandingan Metode Profile Matching Dengan Metode SMART Untuk Seleksi Asisten Laboratorium - Sri Rahayu Astari; Rusydi Umar; Sunardi (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Laboratory assistant in university are the main factors in determining the course of practical in the laboratory. So it needs to be selected to get an assistant with good competence. Assistant selection is done by assessing four aspects namely administration, competence, microteaching, and interview. So far the assessment is still done manually, the criteria value still has the same importance. The calculation method which is also not optimal has an impact on the results and the long time of decision making. So we need a method to overcome these problems. In this study the calculation methods used are Profile Matching and SMART (Simple Multi Attribute Rating Technique). Based on research conducted both methods work by grouping criteria according to their level of importance. There are 12 criteria divided into four aspects, and alternative data of 7 participants were taken from 2019 participant data. The results of the two methods are ranking sequences compared with ranking results in 2019 selection. The results of this study show better profile matching because it has an accuracy value 100% is exactly the same as the results of the previous selection, while SMART is only 42.8%.